Legal Protection for Malnourished Children for Fulfillment of Health Services - Amelia Pranita Ikhsan; Hasbir Paserangi; Muh Hasrul (UIN Sunan Gunung Djati, 2022)
A child whose health is disturbed, both physically and psychologically is a reflection of not achieving the child's welfare. To get the welfare of the child, every child has the right to get services from the government and the community. The government stipulates laws and regulations in order to enforce the right of children to obtain health services. However, the reality that occurs in the community is that children do not get maximum nutritional health services both at the puskesmas and hospital levels so that there is no decrease in the number of children suffering from malnutrition. There is a need for legal protection for malnourished children so that children's welfare can maximize the growth and development process properly. In this case, the law is tasked with ensuring the welfare of children and guarding the interests of children in providing child protection. This study uses a qualitative approach with empirical legal research techniques in data collection and uses content analysis in describing the data obtained. The results of the study found that the legal protection for malnourished children for the fulfillment of health services in the prevention of malnutrition in children who were not carried out optimally. Various cross-sectoral roles are needed in the effort to fulfill the rights of malnourished children. The implementation of legal health services based on Health Law no. 36 of 2009 must be implemented, especially in overcoming the problem of malnutrition so that all health problems can be overcome in an effort to overcome malnutrition.